Land Status Arises Law (Aanslibbing) Which Is Controlled By The People Of Muarabaru Village, Cilamaya Wetan Kabupaten Karawang District, Is Associated With Government Regulation No. 16 Of 2004 Concerning Land Stewardship - Saim Aksinuddin (IHSA Institute, 2022)
The purpose of this study was to find out and analyze how land status arises law (aanslibbing) which is controlled by the people of muarabaru village, cilamaya wetan kabupaten karawang district, is associated with government regulation no. 16 of 2004 concerning land stewardship. The research used is descriptive analysis, which describes systematically the data on the problem to be discussed. Analytical descriptive specifications of research methods aimed at describing the facts that occur, and not only describe the results of the research, but also examine in line with government regulation number 16 of 2004 concerning land stewardship and other laws and regulations as well as legal theory and practice of implementing positive law, so that answers can be found to the problem of legal protection of land tenure arises. The results of the study prove Legal Status of Emerging Land (Aanslibbing) Controlled, Mechanism for Obtaining Arisen Land (Aanslibbing) According to the Customs of the People, And Settlement arising from land arises (Aanslibbing) which is controlled by the community of Muarabaru Village, Cilamaya Wetan District, Karawang Regency.